Значення задоволення у філософії Епікура - Червінська, A. (ХНУРЕ, 2022)
Life is a unique good, the main pleasure that people have. The Epicureans revered and loved life. However, they all understood that this benefit was shortlived. Human life is only an episode compared to the boundless nature. Epicurus considered it a false belief that the immortal essence of a living being is reincarnated again and again from one body to another. From this discovery, it is concluded that it is very important to give yourself completely to the current moment, and not wait until the next one comes. You need to fully immerse yourself and enjoy what is happening at the moment
Keywords: значення задоволення